Comparing the Effect of Intrathecal Injection of Pethidine with That of Bupivacaine on Hemodynamics in Hip Surgery: A Double Blinded Clinical Trial - Seyed Babak Mojaveraghili; Sina Hassannasab; Mansour Deylami; Tahereh Chavoshi; Avasadat Mirkatouli; Nasser Behnampour (Archives of Anesthesia and Critical Care)
Background: The use of regional anesthesia for lower limb orthopedic surgery is preferable to general anesthesia. In some studies comparing regional anesthesia and general anesthesia, the one-month mortality of patients undergoing regional surgery was significantly lower. Given the relative advantages observed about intrathecal injection of pethidine, including fewer side effects, and longer postoperative analgesia, in combination with effective sensory, motor, and sympathetic blocks, we sought to compare the influence of intrathecal injection of pethidine and bupivacaine on the hemodynamics of patients. Methods: In this double blind randomized parallel trial, patients undergoing surgery with femoral and hip fractures, were divided into two groups. In the first group bupivacaine and in the second group pethidine were used for spinal anesthesia. Hemodynamic changes were examined and recorded during surgery. The results were analyzed by SPSS18 software Results: 67 patients undergoing surgery with femoral and hip fractures, were divided into two groups of 30 and 37 individuals. The mean heart rate in patients with a high risk of surgery was higher in the group receiving pethidine compared to the group of bupivacaine, with a Cohen's effect size of 0.294. This effect size is evaluated as average, while the rate of mean arterial pressure with Cohen's effect size of 0.511 was evaluated as large. Conclusion: Pethidine can be a good alternative to bupivacaine, especially in patients at high risk of surgery, given its hemodynamic stability.